Insight into Biological Apatite: Physiochemical Properties and Preparation Approaches. (1st September 2013) - Liu, Quan; Huang, Shishu; Matinlinna, Jukka Pekka; Chen, Zhuofan; Pan, Haobo
Abstract : Biological apatite is an inorganic calcium phosphate salt in apatite form and nano size with a biological derivation. It is also the main inorganic component of biological hard tissues such as bones and teeth of vertebrates. Consequently, biological apatite has a wide application in dentistry and orthopedics by using as dental fillers and bone substitutes for bone reconstruction and regeneration. Given this, it is of great significance to obtain a comprehensive understanding of its physiochemical and biological properties. However, upon the previous studies, inconsistent and inadequate data of such basic properties as the morphology, crystal size, chemical compositions, and solubility of biological apatite were reported. This may be ascribed to the differences in the source of raw materials that biological apatite are made from, as well as the effect of the preparation approaches. Hence, this paper is to provide some insights rather than a thorough review of the physiochemical properties as well as the advantages and drawbacks of various preparation methods of biological apatite.